Air‐mass origin in the tropical lower stratosphere: The influence of Asian boundary layer air. Issue 10 (27th May 2015) - Orbe, Clara; Waugh, Darryn W.; Newman, Paul A.
Abstract A climatology of air‐mass origin in the tropical lower stratosphere is presented for the Goddard Earth Observing System Chemistry Climate Model. During late boreal summer and fall, air‐mass fractions reveal that as much as 20% of the air in the tropical lower stratosphere last contacted the planetary boundary layer (PBL) over Asia; by comparison, the air‐mass fractions corresponding to last PBL contact over North America and over Europe are negligible. Asian air reaches the extratropical tropopause within a few days of leaving the boundary layer and is quasi‐horizontally transported into the tropical lower stratosphere, where it persists until January. The rapid injection of Asian air into the lower stratosphere—and its persistence in the deep tropics through late (boreal) winter—is important as industrial emissions over East Asia continue to increase. Hence, the Asian monsoon may play an increasingly important role in shaping stratospheric composition.